Design: a partner for the development of twenty-first century skills - Brancoli, Bernardita (Base Diseño e Innovación, 2016)
We are living a change in education. In the face of the new challenges that future jobs will demand, students need to update their skills and competencies. The use of technologies, the increase in life expectancy and the interconnection of markets, coupled with social values that require a more equitable and sustainable world, require multidimensional educational tools. These will enable children and young people of the future to apply them in multiple contexts, within globalization.